Curved Damper as Structural Retrofitting Element to Improve the Performance of Steel Truss Bridge - Ummati, Alfinna Mahya; Wirawan, Nugraha Bintang; Halim, Hendra (Rekayasa Sipil, 2024)
The curved damper can control the structure movement by a physical approach to reduce the lateral deformation under the earthquake, which previously proved to be a significant improvement when applied on a moment-resisting frame in a laboratory scale experiment. With the same idea, a curved damper is considered a passive control to reduce the excessive deformation for a single span of a steel truss bridge, which is analyzed by finite element modeling to evaluate the role of the curved damper in a complex structure. The study of curved dampers applied in this typical bridge showed that mid-span deformation can be mitigated by up to 62% under an earthquake. Hence, a structure with a curved damper is recommended for application in high seismic locations.